Spatial Distribution Recast for Organic Bulk Heterojunctions for High‐Performance All‐Inorganic Perovskite/Organic Integrated Solar Cells. Issue 35 (2nd August 2020) - Chen, Weijie; Li, Dong; Chen, Shanshan; Liu, Shuo; Shen, Yunxiu; Zeng, Guang; Zhu, Xiaozhang; Zhou, Erjun; Jiang, Lin; Li, Yaowen; Li, Yongfang
Abstract: All‐inorganic CsPbIBr2 perovskite solar cells (pero‐SCs) exhibit excellent overall stability, but their power conversion efficiencies (PCEs) are greatly limited by their wide bandgaps. Integrated solar cells (ISCs) are considered to be an emergent technology that could extend their photoresponse by directly stacking two distinct photoactive layers with complementary bandgaps. However, rising photocurrents always sacrifice other photovoltaic parameters, thereby leading to an unsatisfactory PCE. Here, a recast strategy is proposed to optimize the spatial distribution components of low‐bandgap organic bulk‐heterojunction (BHJ) film, and is combined with an all‐inorganic perovskite to construct perovskite/BHJ ISCs. With this strategy, the integrated perovskite/BHJ film with a top‐enriched donor‐material spatial distribution is shown to effectively improve ambipolar charge transport behavior and suppress charge carrier recombination. For the first time, the ISC is not only significantly extended and enhanced the photoresponse achieving a 20% increase in current density, but also exhibits a high open‐circuit voltage and fill factor at the same time. As a result, a record PCE of 11.08% based on CsPbIBr2 pero‐SCs is realized; it simultaneously shows excellent long‐term stability against heat and ultraviolet light. Abstract : A recast strategy is proposed to optimize the spatial distribution of components in organic bulk‐heterojunction (BHJ) films in an all‐inorganic perovskite/BHJ integrated solar cells, leading to extended photoresponse, enhanced ambipolar charge transport, and suppressed charge carrier recombination. A record power conversion efficiency of 11.08% and robust thermal stability are obtained.